Association of orthorexic tendencies with social media addiction, eating attitudes and body perception - Yılmaz, Hamdi; Ünal, Gonca Ayşe (Journal of Dependence, 2024)
Objective: This study aimed to determine the relationship between orthorexia nervosa and social media addiction, eating attitudes and body perception in the general population. Method: In this cross-sectional study, 345 individuals without mental illness according to the Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) participated. Data were collected using sociodemographic data form, orthorexia nervosa inventory (ONE), social media addiction scale (SMBI), eating attitude test (EAT), and body perception scale (BPS). Results: Of the 345 participants, 163 (47.2%) were female and 182 (52.8%) were male. The orthorectic symptoms of individuals who followed healthy eating programs on social media were higher than those who did not. In correlation analyses, ONE was positively correlated with SMBI and EAT and negatively correlated with BPS. When orthorectic symptoms were analyzed according to dependency level, orthorectic symptoms of moderately dependent and highly dependent individuals were higher than those of low dependent individuals, and orthorectic symptoms of low dependent individuals were higher than those of non-addicted individuals. In multiple linear regression analyses, the conflict subscale of the SMBI and the EAT scores predicted the ONE total scores and these variables explained 26.6% of the variance. Conclusion: Orthorectic symptoms were positively associated with social media addiction, impaired eating attitudes and low body perception. The available data suggest that social media can affect mental health. Social media literacy should be encouraged and awareness of orthorexia nervosa should be increased.